Analysis of Language Errors at the Level of Phonology and Morphology in Letters of SDN 02 Bulurejo as a Learning Effort in the Field of Language - Al Maarif, M. Furqon; Nurni, Talitha Amalia; Ulya, Chafit (Lembaga Pendidikan Hikmatun Najah Blora, 2022)
This study aims to analyze language errors at the phonological and morphological levels of official correspondence at SDN 02 Bulurejo from July to July. October 2022. This research uses a qualitative approach, namely a research method used to examine the conditions of natural objects, where the researcher is the key instrument. Based on the results of the research analysis, there are 3 types of errors in language. These three fields can be classified into four phonological errors, four morphological errors, and three spelling errors. With this research, it is hoped that more attention can be paid to writing official letters, especially in the field of morphological phonology and spelling errors.